THE USE OF DERIVATIONAL SUFFIXES STRATEGY TO ENHANCE STUDENTS’ MORPHOLOGICAL AWARENESS OF VOCABULARY MASTERY AT SMP SANTO PETRUS MEDAN IN THE ACADEMIC YEAR 2017/2018 - Tarigan, Karisma Erikson; Stevani, Margaret (Unversitas Katolik Santo Thomas, 2020)
Vocabulary learning plays an important role in vocabulary acquisition, one possible way to achieve it is by using derivational suffixes. The purpose of the study is to know the students’ responses after they are taught with affixation strategy. The subject of this study is the students of Class IX-1 of SMP Santo Petrus Medan in the academic year of 2017/2018. This study is conducted by applying descriptive qualitative research and in the form of survey research. (The instruments of collecting data are quantitative data (questionnaire) and qualitative data (field notes). The result of questionnaire shows that most of the students choose item Strongly Agree whose percentage is 85.79% and item Agree whose percentage is 14.20%. This finding proves that the students’ learning behavior changed positively, that is, their attitude and motivation heightened significantly by using derivational suffixes strategy to teach vocabulary. The data of students’ morphological awareness response of the use of derivational suffixes shows that: (1) Affixation helps to remember English vocabulary better, (2) Affixation helps connect vocabulary with its meaning, (3) Affixation helps to develop vocabulary, (4) Affixation helps to recognize noun, verb, adjective, and adverb, (5) Affixation helps to separate form and meaning between root and affix, (6) The rules of affixation make students understand the good spelling of vocabulary, and (7) Affixation supports English learning. These indicate that there is a significant improvement of the students’ vocabulary mastery through derivational suffixes strategy of Class IX-1 of SMP Santo Petrus Medan in the academic year of 2017/2018.